The role of traditional healing in developing rehabilitation processes and its contributions toward development : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Kwok, King Yu (Massey University, 1993)
The emphasis on Western ways of biomedical health care and rehabilitation has met with problems of practicability in many parts of the world, and particularly problems with those issues related to culture. Reform in rehabilitation and health care should be carried out according to the thinking of people. Being culturally acceptable with philosophies of people, traditional healing can be an invaluable means for innovative rehabilitation health care. Attention to the needs of minority groups, for example, people with disabilities and ethnic minorities, is essential. This thesis sets out a new and innovative rehabilitation model of Individual-Rehabilitation-Society for the use of traditional healing in developing rehabilitation processes. The new model is conceptualized in general systems theory and a basic needs approach. "Think globally and act locally" is the key phrase for health care and development. The contributions of traditional healing and rehabilitation toward development are also discussed.
Keywords: Economic development; Health aspects; Hawaii; Health hygiene; Traditional medicine; People with disabilities; Rehabilitation